2011
DOI: 10.1177/0037549711400777
|View full text |Cite
|
Sign up to set email alerts
|

A software architecture to ease the development of distributed simulation systems

Abstract: The simulation of modern systems may require an amount of computational resources that might not be available on a single host. Distributed simulation (DS) provides an effective way to scale up for the increased computational requirements. However, using existing DS environments remains the main obstacle to the wide adoption of DS systems, because of their inherent complexity. This complexity can be quantitatively shown by the extra effort that the development of DS systems requires compared to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The simulation approach suggested by Bocciarrelli et al, that utilizes the BPMN extension PyBPM, develops and refines a business process simulator for performing the simulation step (Bocciarelli et al 2012(Bocciarelli et al , 2014a. The simulation code as result of transforming a BPMN 2.0 model is executed in a research prototype built on top of a layered software architecture called SimArch that provides a general-purpose and event-based simulation infrastructure for distributed discrete event simulation (Gianni et al 2011). Antonacci et al (2016) build on the approach suggested in Bocciarelli et al (2014a, b, c) and propose to perform simulation by executing eBPMN simulation code in a research prototype, also built on top of SimArch.…”
Section: Tool Support For Bpsmentioning
confidence: 99%
“…The simulation approach suggested by Bocciarrelli et al, that utilizes the BPMN extension PyBPM, develops and refines a business process simulator for performing the simulation step (Bocciarelli et al 2012(Bocciarelli et al , 2014a. The simulation code as result of transforming a BPMN 2.0 model is executed in a research prototype built on top of a layered software architecture called SimArch that provides a general-purpose and event-based simulation infrastructure for distributed discrete event simulation (Gianni et al 2011). Antonacci et al (2016) build on the approach suggested in Bocciarelli et al (2014a, b, c) and propose to perform simulation by executing eBPMN simulation code in a research prototype, also built on top of SimArch.…”
Section: Tool Support For Bpsmentioning
confidence: 99%
“…The eBPMN language has been built on top of SimArch (Gianni et al 2011), a layered software architecture that provides an event-driven simulation engine to execute simulation models in either local or distributed simulation environments. eBPMN consists of a set of Java-based primitives that implement the execution semantics of BPMN constructs.…”
Section: Ebpmn-based Model-driven Frameworkmentioning
confidence: 99%
“…As afore mentioned, we restrict our analysis to the IEEE HLA Standard and to the case of conservative execution using DS implementation technologies in which only safe events are processed, such as the SimArch technology (https://sites.google.com/site/simulationarchitecture/simarch) (Gianni et al 2011). …”
Section: Gianni Bocciarelli and D'ambrogiomentioning
confidence: 99%
“…In Step 2, we have used the above mentioned SimArch technology for the rapid prototyping of the DS model (Gianni et al 2011). At…”
Section: Preliminary Validationmentioning
confidence: 99%
See 1 more Smart Citation